Effect of Si3N4 content on microstructures and antioxidant properties of MoSi2/Si3N4 composite coatings on Mo substrate. Issue 10 (December 2015) - Huang, Yu; Lin, Jia; Zhang, Houan
Abstract: To determine the effective content of Si3 N4 on microstructures and antioxidant properties of MoSi2 /Si3 N4 composite coatings on Mo substrate, the MoSi2 – x vol% Si3 N4 /Mo ( x =0, 2.0, 3.5, 5.0, and 8.0) diffusion couples were fabricated by spark plasma sintering and annealed at a temperature of 1300 °C for various periods of time up to 168 h. The interfacial diffusion between MoSi2 –Si3 N4 phase and Mo substrate was examined. Using scanning electron microscopy, the observation of intermediate phases indicated two different mechanisms in Mo5 Si3 phase growth. The degradation rates of MoSi2 phase in MoSi2 – x vol% Si3 N4 diffusion couples were calculated, and the expected Si3 N4 content of MoSi2 –Si3 N4 composite coating was 3.5 vol%.